Studi Komparatif Pengelolaan Keuangan Pribadi Ditinjau Dari Pengetahuan Keuangan Dan Jenis Kelamin - Leli Lutiah Sani; Heti Suherti; Iis Aisyah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study aims to determine differences in personal financial management in terms of financial knowledge and gender of ASN teachers in Panumbangan District. This study used a comparative research method with a comparative design and data collection techniques using a questionnaire (questionnaire). The sample used in this study was 145 ASN teachers. The sampling technique used simple random sampling so that a total of 62 male ASN teachers and 83 female ASN teachers were obtained. The results of this study indicate that there are differences in the personal financial management of men and women, there are differences in the financial knowledge of men and women and differences in financial management based on financial knowledge. The results of the Independent Samples T Test on the personal financial management variable obtained a significance value of (2-Tailed) 0.000 <0.05 and the financial knowledge variable obtained a significance value of (2-Tailed) 0.000 <0.05. This means that there are differences in financial knowledge and financial management. In addition, it can also be seen that financial knowledge has a significant influence on personal financial management.